Climate change impact on ecosystems of Prince Edward Islands: role of oceanic mesoscale processes - Asdar, Sarah (Department of Oceanography, 2019)
The subantarctic Prince Edward Islands (PEIs, 47◦S-38◦E) are classified as isolated and hostile regions, in which the terrestrial and marine ecosystems are relatively simple and extremely sensitive to perturbations. The island’s location, between the Subantarctic Front (SAF) and the Polar Front (PF), bordering the Antarctic Circumpolar Current (ACC) provides an ideal natural laboratory for studying how organisms, ecological processes and ecosystems respond to a changing climate in the Southern Ocean. Recent studies have proposed that climate changes reported at the islands may correspond in time to a southward shift of the ACC and in particular of the SAF. This southward migration in the geographic position of major ocean fronts is likely to coincide with dramatic changes in the distribution of species and total productivity of this region. However, there are other sources of variability in the hydrodynamic conditions around the PEIs: upstream of the islands, at the South West Indian Ridge (SWIR), a region of high eddy kinetic activity produces mesoscale features that directly irrigate the PEIs and may impact their marine environment. Based on satellite altimetry in that region, the positions of the SAF and PF were found to be highly variable at interannual and monthly time scales. They also revealed a significant long-term southward trend which was highlighted at the Southern Ocean scale. The mesoscale activity also showed an interannual and intra-annual variability and a decrease in eddy kinetic energy over 24 years was observed in the region. At a more local scale, we highlighted that the archipelago’s environment was impacted by the mesoscale features produced at the SWIR. The temperature, the mixed layer and velocities recorded between the islands were clearly affected by the eddies passing in the vicinity of the PEIs. Moreover, a large signal dominating the main current time series appeared to be a tidal signal, another important driver of variability of the circulation in between the two islands. On a second hand, an idealised model configuration was designed for the PEIs region to study the mesoscale eddy properties and the physical mechanisms of their formation at the ridge. The Eddy Available Potential Energy revealed a maximum of energy around 800 m depth, confirming the deep reaching characteristic of the eddy originated in the region and suggested the presence of a local energy source at this depth. This eddies activity was shown to be the result of a combination of barotropic and baroclinic instabilities occurring at the ridge. Finally, we investigated on the potential consequences of a southward shift of the SAF in the region of the islands. Because the model was idealised, it allowed us to simulate an SAF southward shift by shifting the initial and boundary conditions. The main result was the clear decrease of mesoscale activity in the region which could potentially impact the ecosystems of the PEIs.